Thiol-functionalized magnetic carbon nanotubes for magnetic micro-solid phase extraction of sulfonamide antibiotics from milks and commercial chicken meat products - Nasir, A.N.M. (2019)
Thiol-functionalized magnetic carbon nanotubes (TMCNTs) were employed as the sorbent in the magnetic micro-solid phase extraction (M-Âµ-SPE) of sulfonamide antibiotics (SAs) in water, milks and chicken meat products prior to high performance liquid chromatography-diode array detector (HPLC-DAD) analysis. The synthesized sorbent was characterized by several spectroscopic techniques. Optimum conditions were: 20 mg of TMCNTs at pH 4, 2 min extraction time, 10 addition of salt and 30 mL of sample volume. Under the optimized TMCNTs-M-Âµ-SPE and HPLC-DAD conditions, the method showed good linearity in the range of 0.1â500 Âµg Lâ1 (r2 â¥ 0.9950), low limits of detection (0.02â1.5 Âµg Lâ1), good analytes recovery (80.7â116.2) and acceptable RSDs (0.3â7.7, n = 15). The method was applied to tap water (1), milks (15) and commercial chicken meat products (35), SAs were detected in five chicken meat samples (3.0â25.7 Âµg Lâ1). The method is critically compared to those reported in the literature. Â© 2018 Elsevier Ltd